«Kashenkin Lug»: Program for Consultative Psychological and Educational Support for Families Having Children with ASD. Evaluation of Efficiency - Pantsyr, S.N.; Krasnoselskaya, E.L.; Danilina, K.K.; Davydova, E.Y.; Khaustov, A.V. (Autizm i narušenie razvitiâ, 2021)
The article presents current understanding of consultation of children with autism spectrum disorders (ASD) in Russia along with the typical contexts in which families looking for help. The necessity of an integrated approach to the organization of consultations shown. We introduce a three-component program of psychological and educational support developed at the Federal Resource Center for Organization of Comprehensive Support to Children with ASD of MSUPE. The program includes a comprehensive psychological and educational examination, the development of an educational route and the feedback receiving, aimed at the analysis of the dynamics of development. The results of the evaluation of the effectiveness of the implementation of the program shown, demonstrating positive dynamics in the development of the child and the emerging needs of the family. We registered change in educational pathways as well as improvement of adaptive behavior. Additionally, we analyzed typical difficulties in following recommendations as reported by parents Освещено современное состояние проблемы оказания консультативной помощи детям с расстройствами аутистического спектра (РАС) в Российской Федерации, описаны типичные ситуации обращения семей за помощью и обоснована необходимость комплексного подхода к организации консультативной помощи. Представлена трехкомпонентная структура программы консультативного психолого-педагогического сопровождения семей, воспитывающих детей с РАС, «Кашенкин луг», разработанной в Федеральном ресурсном центре по организации комплексного сопровождения детей с РАС Московского государственного психолого-педагогического университета. Программа включает комплексное психолого-педагогическое обследование, разработку образовательного маршрута и получение обратной связи для анализа динамики развития. Показаны результаты оценки эффективности программы, демонстрирующие положительную динамику в развитии ребенка и в потребностях семьи. Зафиксированы изменения образовательных маршрутов, выявлена положительная динамика в формировании у детей адаптивных навыков, а также подтверждена востребованность повторных консультаций. Дополнительно проанализированы типичные трудности, возникающие у родителей в процессе реализации полученных рекомендаций.